Guggulsterone phytosomes: A novel approach to alleviate hyperlipidemia in high-fat diet-fed rats - Jamal Basha Dudekula; Jebastin Koilpillai; Damodharan Narayanasamy (Shahrekord University of Medical Sciences, 2024)
Introduction: Guggulsterone, derived from Commiphora mukul, is a potent hypolipidemic medication with low bioavailability and water insolubility. To address these challenges, the study aimed to formulate phytosomes and evaluate the efficacy of guggulsterone phytosomes (GPs) in reducing hyperlipidemia in rats on a high-fat diet. Methods: GPs were formulated by incorporating soya lecithin with a suitable solvent to enhance their efficacy against hyperlipidemia induced by a high-fat diet in rats. The optimized GPs were characterized, and in vitro drug release pattern was examined. The hypolipidemic effect of GPs (25 mg/kg body weight) was evaluated in Sprague Dawley rats over 28 days. Results: The GPs demonstrated favorable entrapment effectiveness with a particle size of 145.4 nm and a zeta potential of -17.8 mV. In terms of drug release, the GPs exhibited better stability and bioavailability, with a release of 92.07 ± 1.67% within 24 hours, compared to pure guggulsterone, which only released 28.07 ± 0.81%. GPs elevated the levels of high-density lipoprotein (HDL) and significantly (P<0.05) reduced triglycerides (TG), low-density lipoprotein (LDL) levels, and total cholesterol (TC), compared to their respective control groups. Moreover, GPs showed substantial (P<0.05) antioxidant activity, reduced steatosis, inflammatory cell, and fat cell infiltration in the liver tissue. Conclusion: GPs exhibited hypolipidemic activity in rats with high-fat diet-induced hyperlipidemia compared to pure guggulsterone. These findings emphasize the potential of GPs as an effective therapeutic intervention for managing hyperlipidemia, surpassing the conventional use of the pure compound.